The Role and Importance of Translation and Translation Studies in Our World (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is concerned with the new trends in the theory of translation concentrating on the shift of research interest from linguistic nature of translation to social cultural and communicative approaches. Taking into consideration the cultural context, background and social situation as prerequisites the researchers should reconsider the very study object which is not just the text linguistics but the semiotic sphere of the text, the relationship between the original and target cultures. The article deals with translation studies in the modern world, a special place is occupied by the study of linguistic aspects ofpeople's interlanguage communication, which is called translation. Literature and culture are enriched through translation.